Validation of Jhulsacast Model using Human Participatory Sensing and Wireless Sensor Networks - Jagyasi, Bhushan; Kumar, Vikrant; Pande, Arun; Singh, Bir Pal; Lal, Mehi; Ahmad, Islam; Lohia, Prakash (Potato Journal, 2016)
A wireless sensor network was deployed using four sensor nodes to collect temperature and humidity data from the farm in a region of interest. This study demonstratedimplementation of the Central Potato Research Institute’s Jhulsacast model for forecasting of potato late blight disease using these sensor observations. A novel human participatory sensing mobile phone application was developed for diagnosis of the disease on experimental basis for a particular farm. The validation of the Jhulsacast model, and its comparison with other models was done using the human participatory sensing approach. The study indicated that unlike the existing methods which relies on disease forecasting to control the plant diseases, the decisions on pesticide application can be made by jointly considering diagnosis and forecasting information.